Digital Based Branding of Tourism and MSME Product in Tasikmadu and Gemaharjo Village, Trenggalek Regency - Dewi, Candra; Rahayudi, Bayu; Mahmudy, Wayan Firdaus; Kurnianingtyas, Diva (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
Tasikmadu and Gemaharjo villages are two villages in Watulimo have considerable potential in tourism and MSME products. However, rural communities including tourism actors, village officials, and MSME players are still unable to maximize the potential of the village, due to the lack of ability of tourism managers and MSME actors in promoting tourism and its products widely. Therefore, this activity intends to increase the knowledge and ability of tourism actors, village officials, and MSME actors from Tasikmadu and Gemaharjo villages in promoting tourism and MSME products. This is done by developing tourism profiles and MSMEs digitally. The evaluation results showed that the activity was quite successful in increasing tourism promotion in Tasikmadu by utilizing the village's Instagram social media. In addition, the success of MSME promotion can also be seen by making logos and packaging for MSME products, both in Tasikmadu and Gemaharjo.